Structural Studies on M. tuberculosis Decaprenyl Phosphoryl-β-D-ribose Epimerase-2 Enzyme Involved in Cell Wall Biogenesis - Gangwar, Shanti P; Bandyopadhyay, Arkita; Saxena, Ajay K (Archives of Clinical and Medical Case Reports, 2025)
The Mycobacterium DprE2 is a NADH-dependent enzyme and converts the decaprenylphosphoryl-β-D-ribose (DPX) to decaprenylphosphoryl- β-D-arabinofuranose (DPA). The FAD-containing oxidoreductase MtbDprE1 and NADH-dependent reductase MtbDprE2 enzymes catalyzes together the epimerization reaction, which coverts DPR to DPA. Here, MtbDprE2 enzyme was purified and structurally characterized using circular dichroism, molecular modelling, and dynamics simulation techniques. The MtbDprE2 was purified, which eluted as oligomer from size exclusion column. The circular dichroism analysis yielded ~ 47.6% α-helix, ~ 19.8% β-sheet and ~ 32.6% random coil structures in MtbDprE2 enzyme and showed highly thermostability. The molecular modelling of MtbDprE2 and its complex with NADH showed that it contains two domains (i) the large domain consists of central twisted seven β-sheets decorated by eight α-helices and (ii) a small domain contains two short α-helices connect by loop. Overall, the MtbDprE2 adopts a typical shortchain dehydrogenase Rossman fold and NADH binds to Asp69, Ser147, Tyr160, Lys164 of catalytic triad and Gly16, Ser19, Glu20, Ile21 of Glyrich motif of MtbDprE2. 1 ns dynamics simulation was performed on apo and NADH bound MtbDprE2, which indicated the small conformational change in ligand binding site, which resulted more closed pocket than open pocket observed in apo enzyme. Small conformational changes were observed in active site residues and orientation between large and small domains of MtbDprE2 upon NADH binding. Current knowledge of MtbDprE2 structure and its NADH binding mechanism will contribute significantly to development of specific inhibitors against M. tuberculosis.